2021
DOI: 10.3390/ijerph18115590
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Physical Activity Participation among Midlife Immigrant Women: A Systematic Review

Abstract: Immigrant women are less likely to be physically active and face many barriers to participation in physical activity. This systematic review aims to identify the influencing factors and adaption approaches of physical activity interventions among midlife immigrant women. A systematic literature search was performed using various databases, such as MEDLINE, PsycINFO, and CINAHL, in February 2021. Studies were included if they investigated midlife immigrant women participating in physical activity interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 65 publications
5
22
0
2
Order By: Relevance
“…As observed in other research [ 11 , 66 ], gender is notably relevant as a health determinant in immigrant populations, with women suffering more health problems [ 67 ], particularly arthrosis, back pain and migraine. These results are in line with those obtained by Zou et al (2021), who performed a systematic review on immigrant women and physical activity [ 68 ]. Immigrant women engage less in physical activities due to barriers related to social determinants, which can in turn have a negative impact on their health.…”
Section: Discussionsupporting
confidence: 92%
“…As observed in other research [ 11 , 66 ], gender is notably relevant as a health determinant in immigrant populations, with women suffering more health problems [ 67 ], particularly arthrosis, back pain and migraine. These results are in line with those obtained by Zou et al (2021), who performed a systematic review on immigrant women and physical activity [ 68 ]. Immigrant women engage less in physical activities due to barriers related to social determinants, which can in turn have a negative impact on their health.…”
Section: Discussionsupporting
confidence: 92%
“…Also, inclusion of only English language studies may have eliminated relevant studies published in other languages. Although included studies were few, we maintained a broad scope and included studies involving both women and men, yielding insight that can be widely applied to the design of PA promotion for adult immigrants, and also highlighting the paucity of research on PA promotion for immigrant women, a group particularly at-risk for low rates of PA [ 9 13 ]. Studies were largely based in the United States, so strategies may not be relevant to immigrants in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…The same was found to be true of immigrant women in Australia, Europe and the United States [ 6 8 ]. A systematic review of 22 studies published since 2000 identified numerous determinants of PA participation among immigrant women including individual (lack of time, health status, motivation), familial (family support) and environmental (seasonality, neighbourhood, social support) factors [ 9 ]. Other studies involving qualitative interviews revealed that gender (sacrifice self-care for household/family), culture (PA not encouraged) and socioeconomic (low-paying/multiple jobs) factors contribute to low PA rates among immigrant women [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework for sessions—reviewing prior weeks’ activities from the treatment manual, considering skill application, and introducing the subsequent activity—was based on the frameworks used in our prior projects and other PP-based interventions in medical settings (Moskowitz et al, 2012 ; Moskowitz et al, 2017 ). This component was specifically customized for midlife adults, based on our review of midlife physical activity literature (Spiteri et al, 2019 ; Zou et al, 2021 ) and a prior midlife study conducted by our team, (Huffman et al, 2021b ) by providing potentially relevant examples and context (e.g. juggling numerous responsibilities, caring for family) and selecting activities that seemed most specific to midlife (e.g.…”
Section: Methodsmentioning
confidence: 99%